2016
DOI: 10.3201/eid2210.151492
|View full text |Cite
|
Sign up to set email alerts
|

Community- and Healthcare-AssociatedClostridium difficileInfections, Finland, 2008−20131

Abstract: Prudent use of antimicrobial drugs in outpatient settings is needed for reducing the burden of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
25
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 34 publications
7
25
1
Order By: Relevance
“…Clostridium difficile infection (CDI) is a major cause of nosocomial illness worldwide. CDI is associated with high rates of mortality and illness ( 1 ) and has a case-fatality rate of up to 14% within 30 days after diagnosis ( 2 ). Disease recurrence further increases illness rates, reduces quality of life, and might occur in up to 27% of the incident cases ( 3 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Clostridium difficile infection (CDI) is a major cause of nosocomial illness worldwide. CDI is associated with high rates of mortality and illness ( 1 ) and has a case-fatality rate of up to 14% within 30 days after diagnosis ( 2 ). Disease recurrence further increases illness rates, reduces quality of life, and might occur in up to 27% of the incident cases ( 3 ).…”
mentioning
confidence: 99%
“…The disease burden of CDI has been well studied in Europe and North America. Although antimicrobial drug stewardship programs have contributed to a decrease in incidence in some countries, such as the United Kingdom and Finland ( 2 , 4 ), CDI is still a major health burden in other countries. In South Korea, a nationwide study showed an increasing trend in incidence of CDI ( 5 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C difficile infection is no longer restricted to hospital settings, and is increasingly prevalent in the community. Currently, more than a quarter of all cases of C difficile infection are estimated to be community acquired,293031 although community acquired infection is still under-recognized because of a lack of screening by community physicians 3233. Epidemiological studies have shown that community associated C difficile infection affects groups not previously at risk (younger patients and those with no exposure to antibiotics in the 12 weeks before infection) 29.…”
Section: Difficile Epidemiologymentioning
confidence: 99%
“…These include RTs 056, 078 and 126 that are commonly associated with infections in farm animals [47]. Changes in clinically relevant types may additionally reflect the significant rise in CAI, which comprises more than 40% of all cases in some studies [48]. Interestingly, within individual countries, particular types appear to dominate, for example 017 isolates account for 20% of Shanghai isolates whilst in Stockholm, 005 strains are prevalent [49]; in Scotland 078 isolates account for over 10% of infections [50].…”
Section: Geographical Distributionmentioning
confidence: 99%